Inter-organisational collaboration in palliative care trajectories for nursing home residents: A nation-wide mixed methods study among key persons. (June 2019) - Hermans, Sofie; Sevenants, Aline; Declercq, Anja; Broeck, Nady V; Deliens, Luc; Cohen, Joachim; Audenhove, Chantal V
Introduction: Multiple care organisations, such as home care services, nursing homes and hospitals, are responsible for providing an appropriate response to the palliative care needs of older people admitted into long-term care facilities. Integrated palliative care aims to provide seamless and continuous care. A possible organisational strategy to help realise integrated palliative care for this population is to create a network in which these organisations collaborate. The aim is to analyse the collaboration processes of the various organisations involved in providing palliative care to nursing home residents. Method: A sequential mixed-methods study, including a survey sent to 502 participants to evaluate the collaboration between home and residential care, and between hospital and residential care, and additionally three focus group interviews involving a purposive selection among the survey participants. Participants are key persons from the nursing homes, hospitals and home care organisations that are part of the 15 Flemish palliative care networks dispersed throughout the region of Flanders, Belgium. Results: Survey data were gathered from 308 key persons (response rate: 61%), and 16 people participated in three focus group interviews. Interpersonal dimensions of collaboration are rated higher than structural dimensions. This effect is statistically significant. Qualitative analyses identified guidelines, education, and information-transfer as structural challenges. Additionally, for further development, members should become acquainted and the network should prioritise the establishment of a communication infrastructure, shared leadership support and formalisation. Discussion: The insights of key persons suggest the need for further structuration and can serve as a guideline for interventions directed at improving inter-organisational collaboration in palliative care trajectories for nursing home residents.